Preconditioning of the generalist herbivore Trialeurodes vaporariorum to greenhouse monocultures and its subsequent performance on wild polycultures. Issue 1 (20th March 2016) - Ovčarenko, Irina; Lindström, Leena; Saikkonen, Kari; Jauhiainen, Lauri; Kaseva, Janne; Vänninen, Irene
Abstract: Generalist herbivores can face many challenges when choosing their host plant. This can be particularly difficult if their choice and performance are affected by host experience. Greenhouse whitefly, Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae), is an invasive generalist herbivore, which has established in year‐round greenhouses at northern latitudes where it cannot overwinter outdoors. It mainly uses crops such as cucumber ( Cucumis sativus L.), tomato ( Solanum lycopersicum L.), and ornamentals as host plants. However, every summer the insect escapes greenhouses and is exposed to natural vegetation. We evaluated the performance of T. vaporariorum on diverse vegetation outside greenhouses after prolonged experience of greenhouse crops. First, we surveyed the vegetation near infested greenhouses. Development success of the insect differed among wild hosts. We identified five new hosts among 12 plant species that bore pupae and were thus considered suitable as the insect's host plants. Members of the Urticaceae and Onagraceae were the most preferred and frequently inhabited by all insect life stages. The highest abundance of insects occurred in plots with low plant species richness, independent of plant family in these habitats. We then studied experimentally the impact of 1 year of preconditioning to one of three common greenhouse crops, cucumber, tomato, or poinsettia ( Euphorbia pulcherrima Willd. ex Klotzsch), on the performance of the preconditioned adults and their progeny on four wild plants. Adults from tomato and poinsettia preferred the novel host species over the species to which they were preconditioned. The whitefly population preconditioned to cucumber was the most fecund on all offered hosts. We conclude that generalist herbivores can have large variation in performance, despite polyphagy, on novel hosts as shown by the variable abundance of T. vaporariorum pupae among outdoor hosts. Furthermore, performance of whiteflies on natural vegetation was affected by experience on greenhouse crops. Based on our observations, we provide insights and recommendations for pest management.